MECHANISMS OF FORMATION OF CLUSTER STRUCTURES IN THE SYSTEM OF PRODUCTION OF AGRICULTURAL PRODUCTS (Development Service Industry Management, 2023)
The article examines the issues of forming cluster-type network organizational structures in the agricultural sector, which ensure the integrated interaction of producers and processors. The author's scheme of the cluster structure of wool production and processing enterprises has been developed, and it is substantiated that thanks to this scheme, it is possible to see how Ukrainian enterprises could function for efficient work and saving resources. A model of a regional cluster to produce sheep products is proposed, with an emphasis on the need for active participation of entrepreneurs and relevant state bodies of the region and municipal districts with agricultural specialization. Prospective factors that can contribute to the formation of a cluster from the point of view of unification of economic interests are highlighted. In particular, the importance of a unified price and marketing policy, expansion of production, and the introduction of innovative technologies through integration and cooperation of production and sales of products on the markets was emphasized. It is substantiated that the implementation of the agricultural cluster formation project has the potential to positively influence the economic development of the region through the promotion of "green" and "rural" tourism, improvement of the social and budgetary situation, as well as improvement of the image of the region. The cluster structure makes it possible to bring agricultural products to the international market already in the second year of operation; in particular, lamb is popular. The proposed project is aimed at satisfying the needs of the population in environmentally friendly products, the needs of light industry enterprises in pure wool and semi-finished products from it, the needs of the medical industry in enzyme raw materials, the needs of agriculture in fertilizers, blood and bone meal, the needs of medicine and health care. I am in raw materials to produce catgut.
Keywords: agricultural sector; sheep breeding; agro-industrial integration; cluster; organizational and economic mechanism